An Analysis of Students’ Barriers in Implementing English Presentations and Online Discussions in ELT Classroom - Prayudha S, Joko (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The ability to communicate effectively in English is crucial for global interaction and success in the workforce. It facilitates clear understanding between speakers and listeners, ensuring the intent and purpose of an utterance are well received. In the context of English language learning, students need to be able to convey messages effectively in presentations and discussions. This research aims to identify the obstacles faced by students when making online presentations and discussions. The research employed a qualitative method with a descriptive approach. The study involved 26 English literature students who were conducting online presentations and discussions. Data was collected through observation and interviews to identify the difficulties faced by students. The data was analyzed using data reduction, data display, and data conclusion. The findings showed that students faced internal and external obstacles when conducting online presentations and discussions. Internal factors included lack of self-confidence, shyness, insufficient understanding of English vocabulary, fluency, and unreadiness to convey messages. External factors were related to technology mastery, an unsupportive environment, and lack of English-speaking practice with peers. Despite these obstacles, students were able to improve their speaking skills through habituation activities.